A novel pseudotype derived of the canine distemper virus for adapter-mediated lentiviral transduction in vivo - Nora Winter; Carolin Kolbe; Shima Ferdos; Larissa Steiner; Nils Bartelsen; Dominik Lock; Fabian Engert; Boris Engels; Mario Assenmacher; Michael Schindler; Ulrich M. Lauer; Thomas Schaser; et al. (Molecular Therapy: Methods & Clinical Development, 2025)
Targeted cell entry with lentiviral vectors (LVs) is one approach to enable efficient and specific gene delivery in the context of immunotherapies, such as chimeric antigen receptor (CAR)-T cell therapy. We have recently shown the generation of CAR-T products with varying CD4:CD8 ratios with our selective, universal Adapter-LV system. However, low viral vector titers limit the clinical and in vivo applications of our measles virus (MV)-based system. Here, we report a novel pseudotype based on canine distemper virus (CDV) for the Adapter-LV system (CDV-Ad-LV) and show improved viral vector yield while maintaining flexibility, selectivity, and transduction efficacy. As for MV, the engineered CDV envelope protein is fused to a single-chain variable fragment that binds biotin in the context of a defined chemical linker. Thereby, Adapter-LVs bind only to biotinylated adapter molecules, which in turn bind the antigen of choice. Besides extensive characterization in vitro, we evaluated transduction in vivo with CDV-Ad-LVs and showed high transduction efficiencies of CD4+ and CD8+ T cells following a single-dose injection into human PBMC-transplanted immunodeficient non-obese diabetic (NOD) SCID gamma (NSG) mice. Hence, CDV-Ad-LVs represent a novel and efficient system for adapter-mediated transduction, which broadens the potential of the Adapter-LV technology, going beyond CAR-T cell therapy applications.